Computational methods for biological problems: membrane proteins promenades - Masone, Diego Fernando (2021)
In this work, we discuss the computational techniques of molecular dynamics and docking as essential tools in the study of the interactions between proteins and membranes. We focus on the cellular mechanisms of the membrane pore and the fusion pore, used by the cell to communicate with its exterior. We look at the cases of two proteins of interest: dynamin and alpha-synuclein, and describe their possible role in membrane events such as fusion, fission, and poration. Finally, we describe some of the most widely used docking and molecular dynamics softwares applied to biological protein and membrane systems.